MEDIATION AS AN ALTERNATIVE TO INTERNATIONAL COMMERCIAL ARBITRATION: ISSUES AND CHALLENGES - Kumar, Satish; Dubey, Arunanshu (ShodhKosh: Journal of Visual and Performing Arts, 2026)
“The method adopted by business parties to dispute resolution has shifted over the previous decade. While conventional conflict resolution techniques such as litigation and arbitration remain popular, commercial parties are increasingly turning to alternative dispute resolution methods to discover ways that better suit their commercial objectives and offer efficient and effective results. Mediation is frequently the solution. Mediation helps the parties to maintain control of the situation and focus on a commercial solution rather than legal action. It has the power to transform a commercial conflict into a business opportunity. As a result, mediation is a primary choice, with arbitration and lawsuit as backup options. In this paper, in addition to describing the features of mediation and how the process works, the benefits, and drawbacks of mediation are explored, as well as ideas for how to encourage mediation in business conflicts.”